The Economic Impact of the Syrian War and the Spread of ISIS - Ianchovichina, Elena; Ivanic, Maros (World Bank, Washington, DC, 2015)
The Syrian war and the subsequent emergence and spread of the Islamic State (ISIS) have transformed the Levant in ways one could not have imagined prior to 2011. As the numbers of dead and of refugees and internally displaced kept climbing, and as families were torn apart and neighborhoods were turned into war zones, economies slumped and regional economic ties broke down. The shock of these events, henceforth referred to as the Levant conflict or war, has changed the region in profound ways, yet there are no systematic evaluations of its economic impact. Our objective was to address this gap and quantify both the direct and indirect economic effects of the war on the countries in the greater Levant--Turkey, the Syrian Arab Republic, Iraq, Jordan, Lebanon, and the Arab Republic of Egypt. It is important to note that the analysis in our paper does not factor in several types of costs. The authors do not assess the cost of delivering basic services to refugees in receiving countries; these costs could be substantial for Jordan, Lebanon, and Turkey. The costs of replenishing depleted human and physical capital in Syria will also be sizable. The authors also ignore important dynamic investment-growth links that may amplify the effects discussed here.